Brokering Intercultural Relations in the Rainbow Nation: Introducing Intercultural Marketing - (:unkn) unknown (My University, 2019)
This paper considers the role of marketing in building intercultural relations in superdiverse, post-colonial societies, using post-apartheid South Africa as a case study. Drawing on neo-institutional theory, we analyze South African advertising campaigns to determine how marketing brokers intercultural relations by legitimizing social meanings conveyed through nation-building ideologies and consumers’ lived experiences. We examine whether marketing outputs align with stages of Rainbow Nation-building strategies and types of consumers’ lived experiences of South Africa’s superdiversity. We then derive a conceptualization of intercultural marketing, which we characterize as an approach focused on brokering meanings of convivial intercultural engagement and collective development of societal welfare goals. We contribute to macromarketing theory, directing attention to the important brokering role marketing has, in bridging conceptions of reconciliatory social development held by public policy makers and by societies’ populations. By conceptualizing intercultural marketing, its goals and tools, we contribute to multiculturally-sensitive marketing research and practice advancement.
Keywords: African Research